2017
DOI: 10.1051/matecconf/20179403007
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on material thickness influence on the AWJ processing quality of an aluminium alloy

Abstract: Abstract. The aim of the current paper is to determine the influence of material thickness on the quality aspects of AWJ processing of the AL6061T651 alloy. The analysis is performed under different working conditions. The parameters taken into account to quantify the quality of processing are those defined in the ISO/WD/TC 44 N 1770 standard: width of the processed surface at the jet inlet (Li), width of the processed surface at the jet outlet (Lo), deviation from perpendicularity (u), inclination angle (Į) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…For TiN/TiAlN, increasing the feed rate increased the perpendicularity error at n = 2000 and 3000 rpm, while the opposite was almost true for TiAlN and TiN at the same speeds. Similar to the cylindricity error, the range of perpendicularity error in the current study was less than that found for aluminum drilled with cryogenic cooling [63], and it was much less than aluminum drilled using abrasive-water-jet machining [65], with the annotation that different federates and spindle speeds were used in the aforementioned studies.…”
Section: Effect Of Cutting Parameters and Tool Coatings On Hole Cylindricity And Perpendicularitysupporting
confidence: 58%
“…For TiN/TiAlN, increasing the feed rate increased the perpendicularity error at n = 2000 and 3000 rpm, while the opposite was almost true for TiAlN and TiN at the same speeds. Similar to the cylindricity error, the range of perpendicularity error in the current study was less than that found for aluminum drilled with cryogenic cooling [63], and it was much less than aluminum drilled using abrasive-water-jet machining [65], with the annotation that different federates and spindle speeds were used in the aforementioned studies.…”
Section: Effect Of Cutting Parameters and Tool Coatings On Hole Cylindricity And Perpendicularitysupporting
confidence: 58%
“…Previous studies investigated the effect of cutting parameters, tool coating, tool geometry, and coolants on hole perpendicularity error for a variety of metallic materials such as steel, aluminum, and titanium alloys [37][38][39][40][41][42][43][44][45][46] and composite materials [36,47]. The studies found that three most significant variables on hole perpendicularity error were cutting speed, feed rate, and depth of cut [40][41][42][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…The most extensively studied use of abrasive-H 2 O-jet technology is in the manufacturing of aluminium alloys. Range of Al alloys investigated in scientific studies is very wide, ranging from approximately unadulterated aluminium alloys (1xxx series) [11,12] to Al-Mg alloys (5xxx series) [11,13,14], Al-Mg-Si alloys (6xxx series) [11,[15][16][17][18][19][20][21][22], and Al-Zn-Mg alloys (7xxx series) [11,23,24]. Table 1.…”
Section: Design Of Experiment-doementioning
confidence: 99%